Financial Literacy, Financial Technology, Financial Self-Efficacy, Income, Lifestyle, And Emotional Intelligence On Financial Management - Bowo Lestono; Lasnoto Lasnoto; Tommy Pusriadi (SEIKO : Journal of Management & Business, 2023)
To ascertain the impact of financial self-efficacy, financial self-awareness, financial technology, income, lifestyle, and emotional intelligence on financial management behavior, this study used quantitative research methods. Teenagers at the Bandung Regency served as the study's subject population. In this study, non-probability purposive sampling was used to select a sample of 2022 respondents. Purposive and non-probability sampling were used to create a sample of 220 respondents for the study. Multiple linear regression was the method of data analysis in this investigation. This study's conclusion suggests that financial management behavior is highly influenced by financial literacy, financial technology, financial self-efficacy, income, lifestyle, and emotional intelligence. The expectation is that teenagers will understand the value of financial literacy and work to develop their understanding of investments and insurance so that they will be able to make sound financial decisions in the future. Kata Kunci: Financial Literacy; Financial Technology; Financial Self-Efficacy